PTH-287 7-year experience with perineal reconstruction following abdominoperineal or multivisceral resection using inferior gluteal artery perforator flaps. (22nd June 2015) - Pramateftakis, M-G; Creasy, H; Roblin, P; Mohanna, P-N; Ross, D; Schizas, A; George, M
Abstract : Introduction: Aim of this study is to present our long-term experience of the use of inferior gluteal artery perforator (IGAP) flaps for the immediate reconstruction of the perineum following excisional surgery. To our knowledge, this is the largest series of immediate perineal reconstruction using IGAP flaps published to date. Method: We performed a retrospective analysis of a group of 142 patients who over a period of 7 years (from April 2007 to April 2014) underwent abdominoperineal resection (57 patients, 40%), multivisceral resection (49 patients, 34.5%), local perineal excision (14 patients, 9.8%), panproctocolectomy (3 patients, 2.1%) and perineal hernia repair (2 patients, 1.4%). The remaining 17 patients of our group (11.9%) underwent various perineal procedures such as fistula resections, pilonidal sinus resections or postoperative perineal sinus resections. We used IGAP flaps to immediately reconstruct the perineal defect of all these patients. 74 patients (52%) were male and 68 female (48%), with a mean age of 60 years (range 19–88). The indication for the excision was rectal cancer in 53 patients (37.3%), recurrent rectal cancer in 27 patients (19%), anal cancer in 12 patients (8.4%), recurrent anal cancer in 11 patients (7.7%), gynaecological malignancy in 8 patients (5.6%), inflammatory bowel disease in 12 patients (8.4%), postoperative wound dehiscence in 3 patients (2.1%) and postoperative perineal sinus formation in 9 patients (6.3%). The remaining 7 patients (4.9%) underwent excision and reconstruction for persistent perineal sinuses or pilonidal sinuses. 111 patients (78%) underwent neoadjuvant chemoradiotherapy. Results: The average length of inpatient stay was 17.6 days (range 3–100). Most patients are still being followed up in our outpatient clinic and are being assessed with regards to pain, discomfort and herniation. The commonest complication observed was a dehiscence of the IGAP flaps, which was observed in 53 patients (37.3%). 44 dehiscence cases were observed following surgery for malignant disease and 9 following surgery for benign disease. 81% of these cases were managed conservatively in the form of simple wound care (dressings), negative-pressure wound dressings (VAC) or primary suturing of the defect. Only 10 of the patients had to be re-operated for debridement, washout and closure or flap revision. A total of 2 patients formed a chronic perineal sinus following dehiscence. Conclusion: Our experience has shown that the IGAP flaps are a safe, robust and reliable option for the reconstruction of the perineum following major excisions, with an acceptable rate of complications when compared to other reconstruction options. Disclosure of interest: None Declared.